Evolution of a Human-Specific Tandem Repeat Associated with ALS - Course, Meredith M. (Am J Hum Genet, 2020)
Tandem repeats are proposed to contribute to human-specific traits, and more than 40 tandem repeat expansions are known to cause neurological disease. Here, we characterize a human-specific 69 bp variable number tandem repeat (VNTR) in the last intron of WDR7, which exhibits striking variability in both copy number and nucleotide composition, as revealed by long-read sequencing. In addition, greater repeat copy number is significantly enriched in three independent cohorts of individuals with sporadic amyotrophic lateral sclerosis (ALS). Each unit of the repeat forms a stem-loop structure with the potential to produce microRNAs, and the repeat RNA can aggregate when expressed in cells. We leveraged its remarkable sequence variability to align the repeat in 288 samples and uncover its mechanism of expansion. We found that the repeat expands in the 3′-5′ direction, in groups of repeat units divisible by two. The expansion patterns we observed were consistent with duplication events, and a replication error called template switching. We also observed that the VNTR is expanded in both Denisovan and Neanderthal genomes but is fixed at one copy or fewer in non-human primates. Evaluating the repeat in 1000 Genomes Project samples reveals that some repeat segments are solely present or absent in certain geographic populations. The large size of the repeat unit in this VNTR, along with our multiplexed sequencing strategy, provides an unprecedented opportunity to study mechanisms of repeat expansion, and a framework for evaluating the roles of VNTRs in human evolution and disease.